The Perfect Test - Dietel, Ron.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Some ten years from today, American schools have tried every possible education fad. Common national standards, year-round schools, takeover of school boards, and even the super-qualified teacher program have failed to improve low U.S. achievement on international assessments. That all changes when Grant and Jennifer Wilson, both Stanford Ph.D. graduates, create what they believe are the perfect tests. The Venus Assessment System, the first national tests in U.S. history, flip American education on its ear, making U.S. students number one in the world in math and science. But then Jennifer Wilson discovers a secret list of names, students who are exceptions to the high-stakes consequences of the test. So secret that some people are willing to kill for it. With a tremendous blending of suspense tied to realistic future events, The Perfect Test will appeal to readers of all types, from educators and parents to simply anyone who loves a great, page-turner. As writer Paul Baker from the University of Wisconsin says, (3z(BLike The Name of the Rose and The Da Vinci Code, this story grabs the reader and won$1 (Bt let go.(3y z(BAt a moment of national testing madness, the [Perfect Test] story-line was both fun and gripping. And like all good mystery/science fiction, educational too. I won$1 (Bt give away the ending.(3y (BDeborah Meier, New York University: teacher, writer, and public activist. Author of In Schools We Trust and Many Children Left Behind (3z(BRon Dietel$1 (Bs The Perfect Test reads like a Stephen King novel. A perfect blend of mystery, action and constant surprises, nicely intertwined in a future world of national high-stakes tests. You won$1 (Bt be able to stop reading it.(3y (BJim Kohlmoos, President, Knowledge Alliance: Research to Action in Education (3z(BReady for a break, for a romp? Pick up Ronald Dietel$1 (Bs biting spoof, The Perfect Test. It$1 (Bs a dystopian vision of a world gone crazy, a science fiction portrait of the future that often comes wickedly close to where we are now. John Merrow, President, Learning Matterss
Keywords: Education; Educational tests and measurements; Education; Assessment, Testing and Evaluation